[Mo6I8]4+ complexes with tetrazolate ligands: [3+2] cycloaddition of aromatic nitriles to [Mo6I8(N3)6]2−. (1st September 2021) - Mironova, Alina; Gushchin, Artem; Abramov, Pavel; Eltsov, Ilia; Ryadun, Alexey; Sokolov, Maxim
Graphical abstract: (Bu4 N)2 [Mo6 I8 (N3 )6 ] undergoes [3+2] cycloaddition with nitriles with the formation of a novel hexakis(tetrazolate)complexes (Bu4 N)2 [Mo6 I8 (N4 C-Ar)6 ] (Ar = C6 H5, C6 F5 ) with 2, 5-aryltetrazolyl ligands. Abstract: (Bu4 N)2 [Mo6 I8 (N3 )6 ] undergoes [3+2] cycloaddition with benzonitrile or 2, 3, 4, 5, 6-pentafluorobenzonitrile in the presence of I2 catalyst with the formation of novel hexakis(tetrazolate)complexes, (Bu4 N)2 [Mo6 I8 (N4 C-Ar)6 ] (Ar = C6 H5 (1 ), C6 F5 (2 )) with coordinated 2, 5-tetrazolyl ligands. The products were characterized by X-ray analysis, NMR, IR and ESI-mass spectrometry. The complexes undergo quasi reversible oxidation and are red-light emissive upon UV photoexcitation.